Virtual advising for high-achieving high school students. (April 2020) - Gurantz, Oded; Pender, Matea; Mabel, Zachary; Larson, Cassandra; Bettinger, Eric
Highlights: High school students offered college counseling via remote communication technologies are more likely to attend selective colleges. There were larger treatment effects for non-white students assigned to non-white advisers, but these results rely on very few advisers. Virtual advising did not produce stronger impacts among academically isolated students who typically have less access to counseling. Abstract: We examine whether virtual advising – college counseling using technology to communicate remotely – increases postsecondary enrollment in selective colleges. We test this approach using a sample of approximately 16, 000 high-achieving, low- and middle-income students identified by the College Board and randomly assigned to receive virtual advising from the College Advising Corps. The offer of virtual advising had no impact on overall college enrollment, but increased enrollment in high graduation rate colleges by 2.7 percentage points (5%), with instrumental variable impacts on treated students of 6.1 percentage points.